Labour and social policies for the green transition A conceptual framework - Keese, Mark (OECD Social, Employment and Migration Working Papers, 2023)
This study sets out a conceptual framework to analyse the impact of climate change and greenhouse gases mitigation efforts on the labour market, migration flows and people's health, as well as the most important policy levers that can cushion potential negative impacts and maximise opportunities from the climate transition